The need for prior land regularization in areas with wind potential as a mechanism to protect squatters in the face of the energy expansion process: the case of Santa Luzia, Paraíba, Brazil - Maia, Fernando Joaquim Ferreira; Basso, Ana Paula; Souza, Karolina Maria Fonseca de (Geografares, 2024)
It is analyzed in this paper the previous land regularization in areas with wind potential in the municipality of Santa Luzia-PB. The work is justified by the need of studies that analyze the land aspect of the installation of wind farms. The problem is that the absorption of capital surpluses has distorted land regularization. How important is prior land regularization for squatters in areas with wind potential? The objective is to investigate whether prior land regularization can protect squatters when negotiating with companies. The method is based on studies by Mariana Traldi (2022) and the research methodology involves collecting and processing data based on legislation, jurisprudence, books and scientific articles related to the topic, in addition to studying the case of Santa Luzia. The hypothesis is that prior land regularization can provide more legal security to squatters in negotiations with companies for the implementation of wind turbines on their properties.
Keywords: land regularization; wind energy; Santa Luzia/PB